A 'Baby GDA': Norwich's Airspace during the Second World War. (3rd July 2018) - Gregory, Derwin
ABSTRACT: Throughout the Second World War, the Luftwaffe attacked Norwich on various occasions. The impact this had on the city was recorded visually on the 'Norwich Bomb Map'. This cartographic depiction, however, only records a single 'horizontal' component of the aerial 'battlescape'. In reality, the aerial battlefield comprised a combination of Norwich's air defences and the flightpaths of the Luftwaffe bombers, which existed in three-dimensional space. As other scholars have developed methodologies for reconstructing anti-aircraft 'fire domes', this article will combine these concepts with a new approach that reconstructs historic flightpaths to give a three-dimensional overview of Norwich's 'Gun Defended Area'. By examining all components of Norwich's airspace, this article will demonstrate the importance of considering the vertical component of a battlescape.